Assessing Knowledge and Adoption of Fish Farmers about Fish ProductionTechnology in Madhya Pradesh - Rajan, Parvez; Dubey, M.K.; Agrawal, Sonam; Chauhan, Sandeep (Indian Journal of Extension Education, 2011)
Fishery plays a very important role in the socio-economic development of nation through employment generation, contribution to food security and foreign exchange. The present study was undertaken to assess the knowledge level and adoption of fish farmers about fish production technology. The study was conducted with 90 fish farmers randomly selected in 3 villages of Jabalpur district, which were results showed that. Fish farmers in Jabalpur were of comparatively young age group, education up to high school, low annual income, common pond for fish farming, minimum experience of 15 years, fish farming + singhara cultivation as their main occupation, low attitude towards fish farming, medium market orientation, high scientific orientation, low aspiration level, low use of information sources and training exposure. The knowledge level and adoption of fish farmers about recommended fish practices was medium. It was also observed that there was considerable variation in their knowledge and adoption on different aspects.